EKSAMINASI PUTUSAN SAH ATAU TIDAKNYA PENETAPAN TERSANGKA DEMI KEADILAN (STUDI KASUS PUTUSAN NOMOR 1/PID.PRAP/2022/PN SOS) - Kolono, Sucipto; Sumanto, Listyowati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: This research analyzes the examination of pretrial decisions regarding whether or not the determination of a suspect in a criminal corruption case is valid or not. The case study discussed is Pretrial Decision Number 1/Pid.Prap/2022/PN Sos which decided on the validity of the suspect's determination without the results of an audit from the Financial Audit Agency (BPK). This normative legal research highlights the role of BPK audits as mandatory evidence in determining state losses in accordance with Law Number 15 of 2006. In-depth analysis shows that the absence of such audits can affect the validity of the investigation process and determining suspects. This study underlines the importance of implementing the principles of presumption of innocence, transparency and compliance with criminal procedural law. Thus, this research contributes to efforts to monitor clean, fair and professional judicial processes in Indonesia.Keywords: Examination, Pretrial, Corruption Crimes, Financial Audit Agency, Determination of Suspects.